PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP FRAUD PADA PERUSAHAAN PERBANKAN - Muzdalifah Muzdalifah (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study was to analyze the effect of good corporate governance (GCG) againts fraud on companies listed on the IDX. The data in this study were obtained from compulsory taxes obtained at the North Makassar KPP that were received as respondents. This study uses secondary data with a purposive sampling method with several criteria, so the sample size is 13 banks. Data analysis method used is regression analysis. The results of this study partially, Good Corporate Governance proves negative and significant effect on fraud.